2023
DOI: 10.3390/ijerph20042989
|View full text |Cite
|
Sign up to set email alerts
|

Time to Lift up COVID-19 Restrictions? Public Support towards Living with the Virus Policy and Associated Factors among Hong Kong General Public

Abstract: The fifth wave of the COVID-19 pandemic has caused an unprecedented toll on Hong Kong. As more countries are starting to lift COVID-19 restrictions, it would be important to understand the public attitudes towards lifting COVID-19 restrictions and to identify its associated factors. The present study examined the level of support towards the living with the virus (LWV) policy for COVID-19 among the public in Hong Kong and to identify the associations between resilient coping, self-efficacy and emotional distre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In contrast, there were worries about potential surges of infections/ deaths and the emergence of highly infectious and severe variants (3). Such positive and negative perceptions might jointly determine the general public's support for the policy, as previous literature reported that positive and negative outcome expectancies of a COVID-19related health policy (e.g., COVID-19 vaccination and social distancing) were associated with the support for the policy (9,20,21). Other perceptions might also count.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In contrast, there were worries about potential surges of infections/ deaths and the emergence of highly infectious and severe variants (3). Such positive and negative perceptions might jointly determine the general public's support for the policy, as previous literature reported that positive and negative outcome expectancies of a COVID-19related health policy (e.g., COVID-19 vaccination and social distancing) were associated with the support for the policy (9,20,21). Other perceptions might also count.…”
Section: Introductionmentioning
confidence: 94%
“…Accordingly, the public’s perceptions of the LWV policy might be associated with their attitude towards the LWV policy and the subsequent policy compliance. However, to our knowledge, no studies have investigated perceptions specific to the LWV policy; our literature search located only two studies that investigated the general emotional and cognitive factors of the public’s support for the LWV policy, including self-efficacy, resilient coping, emotional distress, and illness perceptions of COVID-19 ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhanced transmissibility of the Omicron variant significantly increased the number of infected individuals, which led the general public to think that complete elimination was no longer possible. Hence, the usefulness and sustainability of the dynamic zero-COVID policy has been questioned ( Mo et al, 2023 ). Moreover, the attenuated replication of the Omicron variant in lung cells results in less severe clinical pneumonia compared with prior SARS-CoV-2 variants ( McMahan et al, 2022 ).…”
Section: Challenges To the Dynamic Zero-covid Policymentioning
confidence: 99%
“…The lifting of restrictions has enabled the elderly to resume physical activities, essential for maintaining muscle strength, cardiovascular health, and overall physical capability. Studies show a positive trend in physical activity levels, bene cially impacting the health of the elderly [14] [15]. Regular health check-ups, chronic disease management, and rehabilitation services have become more accessible, contributing to improved health outcomes [16] [17].…”
Section: Introductionmentioning
confidence: 99%